All-solid-state planar integrated lithium ion micro-batteries with extraordinary flexibility and high-temperature performance. (September 2018) - Zheng, Shuanghao; Wu, Zhong-Shuai; Zhou, Feng; Wang, Xiao; Ma, Jiaming; Liu, Cheng; He, Yan-Bing; Bao, Xinhe
Abstract: The relentless development and modularization of electronics have urgently required the all-round improvement of performance, flexibility, safety, miniaturization and integration of micro-batteries. However, traditional cell design in stacked geometry fails to meet these comprehensive demands, especially high-temperature performance. Herein, we report the prototype construction of all-solid-state planar lithium ion micro-batteries (LIMBs), with characteristics of superior volumetric energy density, exceptional flexibility, extraordinary high-temperature performance, and outstanding integration of bipolar cells. The planar LIMBs were manufactured based on the interdigital patterns of lithium titanate nanospheres/graphene as anode and lithium iron phosphate microspheres/graphene as cathode, free of polymer binder and separator, working in ionogel electrolyte. The resulting LIMBs deliver ultrahigh volumetric energy density of 125.5 mWh cm −3, ultralong-term cyclability without capacity loss after 3300 times at room temperature, and outstanding rate capability due to the multi-directional Li-ion diffusion mechanism. Furthermore, our micro-batteries present exceptional flexibility without capacity decay under repeated bending, remarkable high-temperature performance up to 1000 cycles operated at 100 °C, superior miniaturization and simplified modularization of constructing intergrated LIMBs that readily control over the output voltage and capacity, all of which can't be simultaneously achieved by the conventional techniques. Therefore, our planar LIMBs hold tremendous opportunities for future miniaturized and integrated electronics. Graphical abstract: All-solid-state flexible lithium ion micro-batteries were constructed, showing extraordinary energy density of 125–146 mWh cm −3, ultralong-term cyclability, robust flexibility, high-temperature performance at 100 °C, and outstanding integration. fx1 Highlights: All-solid-state flexible planar integrated lithium ion micro-batteries (LIMBs) were designed. LIMBs deliver high volumetric energy density 126 mWh cm -3 and long-term cyclability. LIMBs show outstanding rate capability due to multi-directional Li-ion diffusion mechanism. LIBMs present exceptional flexibility and high-temperature performance up to 100 °C.